Achieving highly efficient all-polymer solar cells by green-solvent-processing under ambient atmosphere. Issue 8 (29th June 2021) - Liu, Bin; Sun, Huiliang; Lee, Jin-Woo; Yang, Jie; Wang, Junwei; Li, Yongchun; Li, Bangbang; Xu, Meng; Liao, Qiaogan; Zhang, Wei; Han, Dongxue; Niu, Li; et al.
Abstract : The nonhalogenated solvent o -XY-processed-all-PSCs achieved a highly-efficient PCE of 15.6% along with decent processability under ambient conditions. Abstract : All-polymer solar cells (all-PSCs) exhibiting superior device stability and mechanical robustness have attracted considerable interest. Emerging polymerized small-molecule acceptors (PSMAs) have promoted the progress of all-PSCs exceeding a power conversion efficiency (PCE) of 14%. However, most of the all-PSCs are processed with halogenated solvents that are hazardous towards humans and the environment. Herein, halogen-free processing solvents of CS2, 1, 2, 4-TMB and o -XY are utilized for producing eco-friendly and highly efficient all-PSCs. In particular, o -XY solvent-processed all-PSCs achieve a high PCE of 15.6%, which is among the highest values in green-solvent-processed all-PSCs to date. Detailed investigations reveal that such enhancement is mainly attributed to the optimal blend morphology and polymer crystalline structures, which is resulted from aggregated structures of polymers formed in o -XY. Importantly, o -XY-processed-all-PSCs are successfully fabricated in ambient conditions, affording a high PCE approaching 15.0%. This work highlights the importance of green solvent strategy in controlling the polymer aggregated structures and blend film morphology of all-PSCs, paving the way towards high-performance and eco-friendly all-PSCs for practical applications.